Real Time Pitch Detection For Vocal Tuning Using FFT Algoritma And Spectrogram - Noak, Devin Reness; Bayu Atmaja Darmawan, I Dewa Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
The song is a means of entertainment most often heard by humans where in the song consists of music and vocals. Good quality music and vocal singers will make a song more pleasant to hear. To make the song sound tunable and in accordance with the rhythm can be done by adjusting the vocals according to the tone of the song. From this we know that measuring sound frequencies needs to be done to determine whether a frequency or period is loud, it can also be used as a tool in vocal training, one of them for vocal tuning applications to find the harmonious sound of the sound. Moreover, it can be used as a learning need in Sound Frequency Processing. Where one of the parts to create a vocal tuning application can be through the Real-time spectrogram program. This RTS uses Pyaudio as sound recording, uses the Python 3.6 programming language and uses the Fast Fourier Transform method which will help when making real-time spectrogram and pitch detection programs. The test results obtained 75% accuracy in real-time pitch detection programs.